Antimicrobial Activities of Garenoxacin (BMS 284756) against Asia-Pacific Region Clinical Isolates from the SENTRY Program, 1999 to 2001 - Christiansen, K. J. (American Society for Microbiology, 2004)
Between 1999 and 2001, 16,731 isolates from the Asia-Pacific Region were tested in the SENTRY Program for susceptibility to six fluoroquinolones including garenoxacin. Garenoxacin was four- to eightfold less active against Enterobacteriaceae than ciprofloxacin, although both drugs inhibited similar percentages at 1 μg/ml. Garenoxacin was more active against gram-positive species than all other fluoroquinolones except gemifloxacin. For Staphylococcus aureus, oxacillin resistance was high in many participating countries (Japan, 67%; Taiwan, 60%; Hong Kong, 55%; Singapore, 52%), with corresponding high levels of ciprofloxacin resistance (57 to 99%) in oxacillin-resistant S. aureus (ORSA). Of the ciprofloxacin-resistant ORSA isolates, the garenoxacin MIC was >4 μg/ml for only 9% of them. For Streptococcus pneumoniae, penicillin nonsusceptibility and macrolide resistance were high in many countries. No relationship was seen between penicillin and garenoxacin susceptibility, with all isolates being susceptible at <2 μg/ml. There was, however, a partial correlation between ciprofloxacin and garenoxacin MICs. For ciprofloxacin-resistant isolates for which garenoxacin MICs were 0.25 to 1 μg/liter, mutations in both the ParC and GyrA regions of the quinolone resistance-determining region could be demonstrated. No mutations conferring high-level resistance were detected. Garenoxacin shows useful activity against a wide range of organisms from the Asia-Pacific region. In particular, it has good activity against S. aureus and S. pneumoniae, although there is evidence that low-level resistance is present in those organisms with ciprofloxacin resistance.